2018
DOI: 10.1002/mc.22878
|View full text |Cite
|
Sign up to set email alerts
|

miR‐9 regulates ferroptosis by targeting glutamic‐oxaloacetic transaminase GOT1 in melanoma

Abstract: Ferroptosis is a recently recognized form of regulated cell death driven by lipid-based reactive oxygen species (ROS) accumulation. However, the molecular mechanisms of ferroptosis regulation are still largely unknown. Here we identified a novel miRNA, miR-9, as an important regulator of ferroptosis by directly targeting GOT1 in melanoma cells. Overexpression of miR-9 suppressed GOT1 by directly binding to its 3'-UTR, which subsequently reduced erastin- and RSL3-induced ferroptosis. Conversely, suppression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 56 publications
0
97
1
Order By: Relevance
“…Knockdown of the transaminase GOT1 could also inhibit cysteine deprivation-induced ferroptosis in MEFs ( Figure 1). 17,20 However, the role of glutaminolysis in ferroptosis regulation is more complex. Glutamate dehydrogenase 1 (GLUD1) converts glutamate into αKG through the glutamate deamination.…”
Section: Glutaminolysis Is Indispensable For Cysteine Deprivation-imentioning
confidence: 99%
“…Knockdown of the transaminase GOT1 could also inhibit cysteine deprivation-induced ferroptosis in MEFs ( Figure 1). 17,20 However, the role of glutaminolysis in ferroptosis regulation is more complex. Glutamate dehydrogenase 1 (GLUD1) converts glutamate into αKG through the glutamate deamination.…”
Section: Glutaminolysis Is Indispensable For Cysteine Deprivation-imentioning
confidence: 99%
“…Ample evidence proves miRNAs as key regulators during hepatocarcinogenesis (Giordano & Columbano, 2013). Interestingly, recent studies have demonstrated that miRNAs, such as miR‐9 (Zhang et al, 2018) and miR‐137 (Luo et al, 2018), participate in ferroptosis. Here, miR‐214‐3p (miR‐214), an upstream regulator of ATF4 (Li et al, 2015; Wang et al, 2013), drew our attention.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, anti-miR-9 treatment allows the production of high levels of α-kG through GOT activity. These findings indicate that miR-9 regulates glutaminolysis through GOT1 ablation, and is considered a negative regulator in melanoma cells [111] (Figure 2).…”
Section: Mir-9mentioning
confidence: 85%